ANALISIS DESKRIFTIF DAN KETERKAITAN ANTARA KARAKTERISTIK KONSUMEN KOPI DAN FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KOPI (Studi Kasus pada Konsumen Warung Dongeng Kopi Jogja di Yogyakarta) - Elly Rasmikayati; Yayat Sukayat; Bobby Rachmat Saefudin (Universitas Galuh, 2023)
Nowadays, coffee is popular increasingly so that more coffee shops are established. Every business provides services, quality and other factors that vary. This diversity causes high competition increasingly so that the actors of a new business have to understand market segmentation and consumer needs. The objectives of this study are: 1) identifying the characteristics of consumers of coffee and the factors that influence purchasing decisions; (2) determine the relationship of consumer characteristics to the factors that influence consumer decisions in purchasing. This research method uses secondary data and literature studies. The number of samples used in this study is one with a sample size is 68. Analysis tools on consumer characteristics and the factors that influence purchasing decisions using descriptive statistics and on the relationship between characteristics and factors that influence purchasing decisions using cross tabulation analysis and chi square test. The analysis shows that the majority of consumers are male, aged 21-24 years, occupations as students and from Yogyakarta. The most influential factor is the service factor and the least effect is the environmental factor. From the results of the cross-tabulation analysis shows that in general, consumer characteristics namely age, sex, occupation and origin have a relationship to factors that influence purchases such as psychological factors, environment, service, marketing, personal and personality, except that personality factors do not have age related. Moreover, sex and age characteristics has the psychological, service and personality as the important consideration.